La sostenibilidad de la deuda pública: el caso del Ecuador - Astorga A, Alfredo (2002)
This paper analyzcs the sustainability of Ecuador's public sector debt. For analytical purposes, the public sector corresponds to the non financial public sector, and dcbt, to that owed to the domestic private sector and to forcign agents. From the study of the customary fiscal policy carried out since the mid 90”s, one concludes that, under reasonable assumptions and alternative scenarios, the same is unsustainable since future primary surpluses are unable to cover he cunent stock of debt. Thca, to make fiscal policy sustainable, an effort to increase revenues and/ or decrease future expenses in proportion to GDP is required. [It is worth noting that the country has undertaken a serious commitment in this direction with the approval on May 2002 of a Fiscal Discipline and Transparency Law, the same that sets limits to the deficit, expenditure growth, and debt of the Central Goverament. Assuming that the remainder of the public sector is financially sustaimable, this law assurcs ex ante the solvency of the State. However, accordine to simulations of the Central Govermment's future accounts.